In Vitro and In Vivo Survey of Ethyl Acetate Extract of Acorus calamus (Sweet Flag) Rhizome on Toxoplasma gondii - Maryam Nikkhoo; Qasem Asgari; Mahmood Reza Moein; Kambiz Yaghoobi; Abbas Gholipour (Journal of Parasitology Research)
Background. Toxoplasmosis is a zoonosis disease that can cause a variety range of manifestations in human specially fetus duration and immunodeficiency conditions. Due to toxicity and side effects of current treatment, we evaluated in vivo and in vitro effects of ethyl acetate extract of Acorus calamus rhizomes (rootstocks) on Toxoplasma gondii. Methods. The plant, Acorus calamus, was collected from Sari, North of Iran in spring season. Ethyl acetate extract was provided from plant rhizomes using Soxhlet apparatus. The total phenolic and flavonoid contents of the extract were measured by the Folin–Ciocalteu method. The mortality effect of different concentrations (1-256 μg/ml) of the extract on Toxoplasma tachyzoites was assessed by flowcytometry and propidium iodide staining. For the therapeutic effect assessment, the tachyzoites were inoculated intraperitoneally to mice, and then these mice were orally and intraperitoneally administered different concentrations (32, 64, 128, and 256 mg/kg) of the extract. Also, an infected group received PBS including DMSO 1% as negative control, and an infected group administered sulfadiazine as positive control. For toxicity evaluation of this extract, a group only received dose 256 mg/kg. Results. The plant extract was rich of phenolic compounds (41.27±0.21 mg/g), whereas it contained fewer amounts of flavonoids (4.79±0.01 mg/g). Results of in vitro experiments showed that there is an inverse relationship between the concentrations and the mortality of the parasites (IC50=200.01±7.74 μg/ml). The highest percentage (62%) of dead tachyzoites was seen at maximum concentration of the extract. A significant longevity (8.9 days) was belonged to mice orally administered extract dose (256 mg/kg/day).Conclusion. The ethyl acetate extract of A. calamus rhizomes had significant anti-Toxoplasma activities either in vitro or in vivo. It may be connected to high amount of phenolic compounds. We suggest that the effects of different fractions and the admin types of the extract will be evaluated on the parasite.